Catalytic pyrolysis of municipal solid waste: Effects of pyrolysis parameters - Almohamadi, H. (Diponegoro University, 2021)
Burning municipal solid waste (MSW) increases CO2, CH4, and SO2 emissions, leading to an increase in global warming, encouraging governments and researchers to search for alternatives. The pyrolysis process converts MSW to oil, gas, and char. This study investigated catalytic and noncatalytic pyrolysis of MSW to produce oil using MgO-based catalysts. The reaction temperature, catalyst loading, and catalyst support were evaluated. Magnesium oxide was supported on active carbon (AC) and Al2O3 to assess the role of support in MgO catalyst activity. The liquid yields varied from 30 to 54 wt based on the experimental conditions. For the noncatalytic pyrolysis experiment, the highest liquid yield was 54 wt at 500 Â°C. The results revealed that adding MgO, MgO/Al2O3, and MgO/AC declines the liquid yield and increases the gas yield. The catalysts exhibited significant deoxygenation activity, which enhances the quality of the pyrolysis oil and increases the heating value of the bio-oil. Of the catalysts that had high deoxygenation activity, MgO/AC had the highest relative yield. The loading of MgO/AC varied from 5 to 30 wt of feed to the pyrolysis reactor. As the catalyst load increases, the liquid yield declines, while the gas and char yields increase. Copyright Â© 2021 by Authors, Published by BCREC Group.